Arbuscular mycorrhizae and dark-septate endophytes on Atriplex cordobensis in saline sites from Argentina - Cofré, María Noelia (2012)
Atriplex cordobensis occurs in salt works and saline soils of northern and central Argentina and is utilized as a forage source; however the mycorrhizal status of this salt bush is unknown. We studied the arbuscular mycorrhizae fungi (AMF) and dark-septate endophytes (DSE) fungi in A. cordobensis analysing infection of the roots and spores in the rhizopheric soil. Soil and root samples were collected during summer 2008 at three different saline sites (Salinas Grandes de Jujuy (SGJ), Quebrada de Cafayate-Salta (QCS) and Salinas Grandes de Córdoba (SGC). Assessment of AMF and DSE colonization were made by washing and staining the roots and the AMF spores number was estimated by standard sieving and decanting methods. The results showed moderate to high levels of AMF colonization as well as significant differences in AM colonization and AMF spores number between sites. Glomus s.l. was the dominant genus in A. cordobensis rhizosphere. DSE colonization did not show significant differences between sites. This study confirmed the occurrence of AMF and DSE in Atriplex cordobensis in stressed environments of Argentina.